MAPPING THE INDONESIAN GOVERNMENT'S POSITION IN THE DECISION-MAKING PROCESS OF WORLD HEALTH ORGANIZATION FRAMEWORK CONVENTION ON TOBACCO CONTROL (WHO FCTC) RATIFICATION - Ahmad Zulfikar (MTCC, John Hopkins n The Union, 2015)
Background: Indonesia is a country with rich natural resources. Tobacco is one of the plants that are cultivated in the tropical climate of Indonesia. Unfortunately, the cultivation of tobacco in Indonesia does not produce varied products, instead, many of the tobacco farmers only serve as a supplier of raw materials for the tobacco industry and this position makes the farmers vulnerable and loses their bargaining power against the industry. On the other hand, tobacco products such as cigarettes contribute big revenues from tobacco excise and becomes an obstacle to tobacco control efforts in Indonesia because their contribution in state revenues reached up to IDR 98,62 trillion in 2013. The risk for tobacco farmers to lose their livelihoods and the contribution of the tobacco industry to state revenues are the reasons various parties reject legalization of the WHO FCTC in Indonesia. This research tried to analyze further the Indonesian government's position towards WHO FCTC. Methods: This research was used qualitative approach and using in-depth interview to collect data from informant. The data was collected to identify the influential factors, key actors and strategy to accelerate the process of ratification of the WHO FCTC. There were informant from the government and non-government organizations (NGOs) selected by purposive sampling to answer the in-depth interview. Analysis was done by filtering method. Results: The research finding showed there is four factors affecting the ratification that are technical feasibility, economic and financial viability, political viability, and administrative operability. But the most influencing factor is the political viability. There are two party that affect the party who support the government and campaign for public health as a priority of the government, while at the other party of the cigarette industry with a variety of efforts to mobilize support for the regulations that could adversely affect its business can be rejected. Moreover, there are two key players in Indonesia's WHO FCTC accession efforts: the Ministry of Health from the government side as the initiator institutions and Muhammadiyah Organization from the non-government side which have commitment to tobacco control by produce the Muhammadiyah Tobacco Control Framework (MTCF) in beginning of 2015. This key players selection based on the organization followers/members/mass, property owned, discipline, leadership, access and internal cohesion. The last was the strategy which consisted of three approaches, that were social from human resource competitiveness, economic from the national health insurance program and political from the post-2015 agenda. Conclusions: It could be concluded that the Indonesian government position in the decision-making process of the WHO FCTC ratification most affected by political SEED RESEARCH GRANT 2015 THE 2ND INDONESIA TOBACCO CONTROL CONVERENCE AND CAPACITY BUILDING PROGRAM 2015 2 viability both the party who pros and cons with this ratification. Then the key players can accelerate the process both Ministry of Health and Muhammadiyah organization. Last but not least, the strategies to accelerate the ratification of the WHO FCTC can be followed through research, and policy advocacy with issues of human resource competitiveness, national health insurance program, and post-2015 agenda. Keywords: Indonesian Government, Decision-making Process, WHO FCTC, Ratification